Validation of an instrument to evaluate health promotion at schools - Raquel Oliveira Pinto; Marcos Pascoal Pattussi; Larissa do Prado Fontoura; Simone Poletto; Valenca Lemes Grapiglia; Alexandre Didó Balbinot; Vanessa Andina Teixeira; Rogério Lessa Horta (Universidade de São Paulo, 2016)
ABSTRACT OBJECTIVE To validate an instrument designed to assess health promotion in the school environment. METHODS A questionnaire, based on guidelines from the World Health Organization and in line with the Brazilian school health context, was developed to validate the research instrument. There were 60 items in the instrument that included 40 questions for the school manager and 20 items with direct observations made by the interviewer. The items' content validation was performed using the Delphi technique, with the instrument being applied in 53 schools from two medium-sized cities in the South region of Brazil. Reliability (Cronbach's alpha and split-half) and validity (principal component analysis) analyses were performed. RESULTS The final instrument remained composed of 28 items, distributed into three dimensions: pedagogical, structural and relational. The resulting components showed good factorial loads (> 0.4) and acceptable reliability (> 0.6) for most items. The pedagogical dimension identifies educational activities regarding drugs and sexuality, violence and prejudice, auto care and peace and quality of life. The structural dimension is comprised of access, sanitary structure, and conservation and equipment. The relational dimension includes relationships within the school and with the community. CONCLUSIONS The proposed instrument presents satisfactory validity and reliability values, which include aspects relevant to promote health in schools. Its use allows the description of the health promotion conditions to which students from each educational institution are exposed. Because this instrument includes items directly observed by the investigator, it should only be used during periods when there are full and regular activities at the school in question.